Three Patterns Programmable Russian Form Functional Electrical Stimulator - Abbas Orand; Genichi Tanino; Hiroyuki Miyasaka; Kotaro Takeda; Shigeru Sonoda (International Journal of Electrical and Computer Engineering (IJECE), 2016)
In this paper, a programmable, multi-pattern, wide frequency and duty cycle range electrical stimulator is presented. Using a programmable micro-controller, two waves of carrier and modulating sources are produced. By modulating the two sources, 3 bi-phasic charge-balanced rectangular, triangular and sinusoidal stimulating patterns are produced. The frequency range of the carrier is fixed at 2.5 kHz and the carrier source frequency can be adjusted between 1 and 500 Hz. The duty cycle of both sources can be adjusted between 10% and 90%.